Prediksi Harapan Hidup Pasien Penderita Hepatitis B Menggunakan Classification and Regression Trees - Saparudin, Ahmad; Maulidina, Tiya; Naufal Fikri, Muqsith; Sumarlin, Doli; Wahyudi, Irvan; Khaira, Ulfa (Prodi Sistem Informasi FST Universitas Jambi, 2018)
Data mining is the two words that are familiar are heard by some people. In the world of business data mining is often utilized to support the company's business strategies or formulate. Not only in business, data mining is also utilized in various other areas of education, agriculture, animal husbandry, and medicine. This research was conducted in the classification of the patient sufferer hepatisis B use classification and refression trees (CART) to generate a decision tree that can be implemented to predict the life expectancy of the patient sufferer hepatitis B. After doing this research, produced a decision tree with 93.6% prediction accuracy.